Implementation of the Counseling Guidance Program in Improving Career Decisions in the Economic Field: Case Study at MAS YPI Batang Kuis - Budi Febriani; Chanra Chanra; Naimah Agustina; Yulhasni Yulhasni; Leli Hasanah Lubis (Edumaspul: Jurnal Pendidikan, 2024)
The aim of the research is to discuss the Implementation of the Counseling Guidance Program in Improving Career Decisions in the Economics Field for students at MAS YPI Batang Kuis. This research uses qualitative methods with case studies. Data was collected through interviews, observation and document analysis. The results of this research indicate that the implementation of the counseling guidance program at MAS YPI Batang Kuis has had a positive impact on students in making career decisions in the economic field. Individual counseling sessions, career seminars and industry visits have proven effective in increasing students' understanding of various career options and assisting them in the decision-making process. Although there are several obstacles such as limited human resources and lack of support from parents, overall this program has succeeded in achieving its goals. Analysis of the factors that influence the effectiveness of counseling guidance programs reveals that the availability and competence of counselors, support from the madrasah, active student participation, parental involvement, and the provision of accurate career information are key factors that need to be considered. Strong support from all related parties and a conducive madrasah environment also play an important role in supporting the success of the counseling guidance program. Based on the results of the case study at MAS YPI Batang Kuis, several recommendations for improving the counseling guidance program in other madrasas have been identified. Increasing the number and competence of counselors, support from madrasas and parents, as well as providing accurate and up-to-date career information are very important to achieve optimal effectiveness. Apart from that, active student participation and the quality of guidance activities must also continue to be improved to provide maximum benefits for students in the career decision making process.